Promosi Dan Informasi Media Audio Visual Berbentuk Video Profile Pada SMK PGRI 11 Ciledug Kota Tangerang - Faisal Rudiansyah Hamzah; Panji Wira Soma; Indri Rahmawati (UNIVERSITAS RAHARJA, 2017)
With the development of information technology in particular in the field of multimedia in such rapid and the longer forms of media information more diverse so that more education institutions boast. Media information and promotion is currently used by SMK PGRI 11 Ciledug Tangerang. The purpose of this research audio visual media into the media information and proper promotion, by controlling hearing and vision in the form of audio visual in order to convey messages can be understood by the public at large. Existing problems, namely the medium used by the SMK PGRI 11 Ciledug Tangerang still use print media such as banners, posters and pamplet are considered less effective and efficient to use while simultaneously promoting the institutions with the best possible audio visual media so that it is selected into a medium of information and promotion of the right, by controlling hearing and vision in the form of audio visual. Because therein lies the message delivery process or how to visualize. At the same time listening and showing the contents of the message to the recipient with information through media menunjangnya, so the design of video media profile that displays the entire scope, advantages and facilities belonging to SMK PGRI 11 Ciledug Tangerang, can be a solution in solving problems in media promotion and information. With this study the author makes with the title